Correlation between Ankle-Brachial Index Score and Diabetic Polyneuropathy Degree of Severity - Uni Gamayani; Miftahurachman Miftahurachman; Nushrotul Lailiyya; Handika Sonjaya Juhana (Faculty of Medicine, Universitas Padjadjaran, 2019)
Diabetic polyneuropathy (DPN) is the most prevalent chronic microvascular complication of type 2 diabetes mellitus (DM). The severity of DPN is categorized based on symptoms, signs, and nerve conduction study (NCS) abnormality into grades 0, 1a, 2a, and 2b. Pathogenesis of DPN consists of metabolic and vascular processes. In addition, macrovascular factor also plays a role in the pathogenesis of DPN. Macrovascular diseases, such as peripheral arterial disease (PAD), could be diagnosed using the ankle brachial index (ABI). Several studies have proven a strong correlation between ABI and DPN; hence, this study aimed to examine the correlation between ABI score and DPN severity. This was a cross sectional analytic study on. 73 type 2 DM patients who met the inclusion and exclusion criteria and visited the outpatient Endocrine Clinic and Neurophysiology laboratory of the Department of Neurology Dr. Hasan Sadikin General Hospital Bandung, during the priod of June to October 2018. ABI examination were performed after DPN indication was evident from results of physical examination, lab tests, and NCS. Rank Spearman statistical analyses were performed to assess the correlation between ABI score with DPN severity and the result was considered significant if p value <0.05. No correlation was found between ABI score DPN severity and between ABI score and DPN symptoms, signs, and NCS abnormality. Hence, ABI score does not correlate with DPN severity stage. Hubungan Skor Ankle-Brachial Index dengan Derajat Keparahan Polineuropati DiabetikaKomplikasi kronis mikrovaskular diabetes mellitus (DM) tipe 2 yang sering ditemukan adalah polineuropati diabetika (PND). Derajat keparahan PND berdasar gejala, tanda, dan abnormalitas pemeriksaan konduksi saraf tepi (KST) dibagi atas derajat 0, 1a, 2a, dan 2b. Patogenesis PND terdiri atas proses metabolik dan vaskular. Faktor makrovaskular diduga memiliki peranan terhadap terjadinya PND. Penyakit arteri perifer oklusif (PAPO) adalah penyakit makrovaskular yang dapat dideteksi dengan pemeriksaan ankle brachial index (ABI). Beberapa penelitian membuktikan hubungan antara skor ABI dan PND. Penelitian ini bertujuan menilai hubungan antara skor ABI dan derajat keparahan PND. Penelitian bersifat observasi analitik studi potong lintang yang dilakukan pada 73 penyandang DM tipe 2 yang memenuhi kriteria inklusi dan eksklusi di Instalasi Rawat Jalan Klinik Endokrin dan Laboratorium Neurofisiologi KSM/Departemen Neurologi RSUP Hasan Sadikin Bandung periode Juni sampai Oktober 2018. Pemeriksaan ABI dilakukan setelah pemeriksaan klinis PND, laboratorium darah, dan KST. Korelasi antara skor ABI dengan derajat keparahan PND dinilai menggunakan analisis statistik Rank Spearman, signifikan jika p <0,05. Tidak terdapat korelasi antara skor ABI dan derajat keparahan PND. Tidak terdapat korelasi gejala PND, tanda PND, maupun abnormalitas uji KST dengan skor ABI. Skor ABI tidak berkorelasi dengan derajat keparahan PND, baik gejala PND, tanda PND, maupun abnormalitas uji KST.